Human factors for the undergraduate aviation student - Higdon, Jami Marie (Kansas State University, 2024)
Many things can influence a student's success in a course. Previous research has shown that students are more successful when they complete the course reading, but students may not always comply with reading requirements for multiple reasons, such as other time pressures or financial costs. Issues with reading requirements may be compounded if an instructor has to re-organize a textbook or supplement a textbook with other materials which may result in confusing reading assignments or extra reading. Students also perform better in well designed courses; however, teachers do not always have the resources to fully design a course before implementation. This may be especially true if a teacher is assigned a course outside of their core subject matter expertise. This curriculum product addresses the design concerns by providing a prescriptive constructive curriculum to teach Human Factors for Undergraduate Aviation Students. The prescriptive aspect of the curriculum is meant to support the instructor, not meant to infringe on academic freedom. Assignments and reading expectations are aligned with industry objectives and designed in accordance with key literature for well designed courses that encourage learning beyond rote memorization.
Keywords: Aviation human factors; Crew resource management; Constructivism